Relationship Between Anti-Virus Drugs And The Incidence Of Herpes Zoster Oticus: Literature Review - Fatmawati, Fatmawati; Nurelly N. Waspodo; Indah Hamriani (Jurnal EduHealth, 2024)
Herpes zoster oticus (HZO) is an infectious disease characterized by an erythematous vesicular eruption or rash on the pinna and external auditory canal along with severe otalgia. Antiviral drugs are very effective in reducing the severity and duration of HZO when treatment is started within 72 hours of the onset of the rash. Objective: This retrospective study summarizes the knowledge of the relationship of antiviral therapy to the incidence of Herpes Zoster Oticus . Method: This article is a literature study or literature review. The literature was obtained by collecting and reviewing Narrative Review, Case Report, Journal Method articles that were downloaded using electronic based accredited/indexed by Scopus and Sinta. Results: In this literature, 20 research articles were obtained discussing herpes zoster oticus and in them discussing treatment using antivirals. Among them consisted of 8 Case reports, 6 Narrative Reviews, and 6 Journal Methods. Conclusion: Antiviral administration in the occurrence of Herpes Zoster Oticus Antiviral administration in cases of Herpes Zoster Oticus is still effective until now. Administration of antivirals as early as possible within 72 hours is effective in reducing the severity of Herpes zoster oticus . Early treatment can stop the invasion and replication of the Varicella zoster virus further into the cranial nerves so that the prognosis for healing nerve function is very good. The combination of Antivirals and corticosteroids is the standard treatment for Herpes zoster oticus which helps full recovery of facial paralysis and inhibits hearing loss. However, from this literature review it is known that the delay in treatment of hearing function experienced will continue.